Reaction of Carbon Dioxide Gas Absorption with Suspension of Calcium Hydroxide in Slurry Reactor - Zahrul Mufrodi; L. M. Shitophyta; Hary Sulistyo; . Rochmadi; Muhammad Aziz (Ital Publication, 2023)
Chemical phenomena involving three phases (solid, liquid, and gas) are often found in the industry. Carbonate (CaCO3) is widely used in industries as a powder-making material in the cosmetic industry, a pigment in the paint industry, and filler in the paper and rubber industry. This research aim to study the ordering process carbonate deposits (CaCO3) from the absorption process of CO2 gas with Ca(OH)2 suspension. The absorption reaction of CO2 gas with Ca(OH)2 suspension was carried out in a stirred slurry tank reactor. Initially, the reactor containing water was heated to a certain temperature, then Ca(OH)2 was added to the reactor. Furthermore, CO2 gas with a certain flow rate and temperature (according to the reactor temperature) is flown with the help of a gas distributor. Samples were taken every 1 min until the concentration of Ca(OH)2 could not be detected (completely reacted). The variables in this study were: stirrer rotation speed (5.66711.067 rps), CO2 gas flow rate (34.0127–60.5503 c/s), and temperature (30–50°C). The mass transfer coefficient and the reaction rate coefficient were determined by minimizing Sum of Squares of Errors (SSE). This experimental process follows a dynamic regime. A dimensionless number relationship for the gas-liquid mass transfer for the value range is Re1 = 18928.76-38217.20, Sh = 0.07928 Reg0.4383 Rel0.4399 Sc0.6415 with an error of 5.19%. The dimensionless number relationship for solid-liquid mass transfer is Sh = 0.0001179 Reg0.4674 Rel0.5403 Sc1.444 with an error of 7.31%. The relationship between the reaction rate constant and the temperature in the 30-50 °C range can be approximated by the Arrhenius equation, namely kr = 1771000 e-2321.4/T cm3/mgmol/s with an error of 3.63%. Doi: 10.28991/ESJ-2023-07-02-02 Full Text: PDF